1992
DOI: 10.3758/bf03209145
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention and perceptual grouping

Abstract: Perceptual organization is thought to involve an analysis of both textural discontinuities and perceptual grouping. In earlier work, we found that textural discontinuities were detected normally even when visual attention was engaged elsewhere. Here we report how perceptual grouping is affected when visual attention is engaged by a concurrent visual task. To elicit perceptual grouping, we used the Gestalt demonstrations of grouping on the basis of proximity and of similarity. Four tasks were investigated, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
86
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 61 publications
13
86
1
Order By: Relevance
“…The poorer performance under the divided-attention conditionreplicated Barchilon Ben-Av et al (1992). What is noteworthy is that poorer performance was obtained even in the large-disparity condition, in which, under full attention, performance was virtually at ceiling level, suggesting that the arrowheads were grouped rather easily.…”
Section: Arrowhead Identificationmentioning
confidence: 90%
See 3 more Smart Citations
“…The poorer performance under the divided-attention conditionreplicated Barchilon Ben-Av et al (1992). What is noteworthy is that poorer performance was obtained even in the large-disparity condition, in which, under full attention, performance was virtually at ceiling level, suggesting that the arrowheads were grouped rather easily.…”
Section: Arrowhead Identificationmentioning
confidence: 90%
“…In an earlier series of experiments in which a dividedattention paradigm was used, Barchilon Ben-Av et al (1992) showed that the grouping operation appeared to demand attentional resources. They compared performance in a dual-task condition, in which the identification of the background pattern constituted the secondary task, with a condition in which it was the main task.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Presumably, this is because they were not attending to the grouping array while their attention was focused on the task-relevant cross. This was taken as evidence that even if a pattern is at the centre of vision, grouping processes may not operate unless attention is specifically allocated to the pattern (also see Ben-Av, Sagi, & Braun, 1992). However, since then, others, using different paradigms, have uncovered evidence, often indirect, that at least some perceptual grouping may be operating pre-attentively (Kimchi, 2009;Lamy, Segal, & Ruderman, 2006;Moore & Egeth, 1997;Russell & Driver, 2005), although this is not the case for all types of grouping (Kimchi & Razpurker-Apfeld, 2004).…”
Section: When Does Grouping Happen?mentioning
confidence: 99%